ANALISIS KINERJA KARYAWAN DENGAN MENGGUNAKAN METODE REGRESI LINIER BERGANDA DI PT. RST - Erfa Inayah; Apid Hapid Maksum (INTECOMS: Journal of Information Technology and Computer Science, 2026)
This study examines the extent to which five variables motivation, work discipline, operational environment conditions, training quality, and compensation schemes influence employee performance at PT RST. The research approach uses a quantitative methodology with a questionnaire instrument, which was distributed to 39 staff in the Stamping Operation Department. Data analysis was conducted through multiple linear regression to measure the influence of each variable and their collective contribution to employee performance. The results of the simultaneous analysis show that the five factors together have a very high explanatory power for performance variations, evidenced by a coefficient of determination (R²) value of 0.994. Partially, each factor motivation, discipline, work environment, training, and compensation shows a positive and significant influence on employee productivity. These findings emphasize the importance of designing data-oriented human resource management policies, where increasing motivation, enforcing discipline, improving work facilities, organizing regular training, and a fair and transparent compensation system are the main pillars in efforts to improve organizational efficiency and output.   Keywords : Work Discipline, Work Environment, Employee Motivation, Employee Training, Compensation System